Insights on Origins, Hosts, Impacts of Banana Anthracnose and its Management (Journal of Agriculture and Biology, 2025)
Banana is a staple food of millions of people in almost all the tropical and subtropical regions of the world. The most critical factors affecting banana production are post-harvest diseases, which generally originate from the flowering to fruit maturity or at the time of harvesting and subsequent storage of fruits. The primary sources of such infection include superficial wounds during handling, leading to enormous economic losses. One major post-harvest pathogen is Colletotrichum musae, causing anthracnose, a pretty significant disease on banana fruits and other plant parts. The pathogen overwinters in plant residues, such as mycelia or sclerotia, produce acervuli that generate primary conidia. Conidia disseminated by rain infect the plant and initiate secondary infection cycles. However, it was mentioned that the growth and pathogenicity of C. musae were highly affected by the following environmental factors: pH and temperature. Moreover, the susceptibility of banana cultivars to anthracnose is varied, with resistant to highly susceptible cultivars. Besides prevailing environmental conditions that favor growth, knowledge of the disease cycle of C. musae becomes essential in devising effective management strategies to reduce post-harvest losses with disease-free bananas.